Is the Balance Sheet Expansions of the Central Banks Inadequate? The Case of Japan - Kurihara, Yutaka (Archives of Business Research, 2024)
The Bank of Japan has continued monetary expansion to combat deflation for over twenty years. However, in March 2024, the Bank raised the negative policy interest rate that had lasted eight years and two months. From now on, the Bank should cope with huge balance sheet expansion. Although yield curve control (YCC) has been abolished, long-term interest rates will continue to be controlled to some degree since the Bank will continue to purchase long-term government bonds. New purchases of exchange-traded funds (ETFs) have been completed, but the main measures of normalization, such as removing ETFs from the huge balance sheet, will not be implemented easily because of increasing risk of stock prices decreasing. Consequently, there will be some possibilities to lead to a rise in long-term interest rates, a strong yen (a decrease in exports), and also to a decline in stock prices. Empirical analyses are conducted to examine the effects of monetary expansion and the results are positive, however, this study emphasizes the importance of the credibility of central banks.